ATTITUDE OF EMPLOYEES ON THE APPLICATION AND SIGNIFICANCE OF HACCP SYSTEM IN RURAL TOURIST HOUSEHOLDS IN SERBIA DURING COVID-19 - Gajic, Tamara; Raljić, Jovanka Popov; Čerović, Slobodan; Aleksić, Milica; Sikimić, Višnja (Economics of Agriculture, 2021)
Diseases caused by food consumed in restaurants during a pandemic, can cause enormous damage and lead to closure of rural households. The aim of the research was to determine the attitude of employees in rural households on the application and importance of doing business according to the HACCP (Hazard Analysis and Critical Control Point) food safety system in 47 rural tourist households in Serbia during the COVID-19 pandemic. A structured field survey questionnaire was conducted on a sample of 286 employees. The generated data were processed by the statistical program Statistica 14.0. The obtained results show that the application of HACCP food safety system during the pandemic was highly appreciated by the employees and that operating according good hygiene practice (GHP) and good manufacturing practice (GMP) fully meets all safety requirements and the extent to which employees in rural households must be aware of and be instructed in its application.